Analysis Internal Factors of Hospitals Affiliated with Kurdistan University of Medical Science Based on Weisberg's Six-Box Model and Its Relation to Their Crisis Preparedness - A A Nasiripour; P Raeissi; N Yazdani (Tehran University of Medical Sciences, 2013)
Abstract Background: Several factors have an impact on hospitals` crisis preparedness including the status of "internal factor ". This study is aimed to investigate the relationship between the status of hospitals `internal factors and their level of preparedness in crisis. Materials and Methods: This correlative, applied, and cross-sectional study was conducted in 12 hospitals of Kurdistan University of Medical Science in 2008. The data were collected using the standard Weisbord questionnaire and hospital preparedness checklist to measure the status of internal factors and the hospitals` level of crisis preparedness ,respectively. The data were analyzed using descriptive and analytical statistical methods. Results: Changing internal factors would result in 74% of the changes in level of hospital preparedness in crisis in all studied hospitals . The preparedness level and the organizational structure of the hospital had strongest relationship and preparedness level and personnel's attitude to changes had the weakest respectively . Conclusions: Hospitals should analyze their internal factors status in order to improve their preparedness level in crisis. Concentrating on different aspects of internal factors, reviewing objectives, improving increasing teamwork, involving personnel in decision-making, using performance-based rewards, forming communication committee, improving leadership styles, training organization `s managers and leaders, and facilitating internal and external coordination could be effective .